Study on Properties of Drainage SBS Modified Asphalt Mixture with Fiber - Zhenxia Li; Tengteng Guo; Yuanzhao Chen; Menghan Zhang; Qingyu Xu; Jing Wang; Lihui Jin (Advances in Civil Engineering)
In order to improve the road performance of drainage SBS modified asphalt mixture, basalt fiber was added to prepare drainage styrene-butadiene-styrene (SBS) modified asphalt mixture. The viscosity-toughness, toughness, and 60°C dynamic viscosity of SBS modified asphalt were tested. The modification effect was evaluated from the perspective of high and low temperature rheological properties by dynamic shear rheometer (DSR) and bending beam rheometer (BBR) tests. The high temperature stability, water stability, low temperature crack resistance, and drainage of basalt fiber SBS drainage asphalt mixture were evaluated and compared with nonfiber SBS drainage asphalt mixture and TPS drainage asphalt mixture. The morphology characteristics of asphalt mixture and the distribution of basalt fiber in the mixture were analyzed from a micro perspective. The results showed the following: the overall performance of basalt fiber is better than that of lignin fiber. SBS modifier content in 7% can meet the requirements of drainage asphalt pavement on asphalt binder. The optimum asphalt content of SBS modified asphalt mixture with basalt fiber content of 0, 0.15, 0.25, and 0.35% is 4.9, 5.05, 5.15, and 5.2%. The fiber is irregularly distributed in the mixture to form a three-dimensional network structure, which has a series skeleton function. It plays a tensile role in the initial cracking of asphalt mixture and prevents further expansion of cracks.